502. CORRELATION OF LYMPH NODE SIZE WITH METASTATIC INVOLVEMENT IN PATIENTS WITH OESOPHAGEAL CANCER. (24th September 2022) - Dutt, Koel; Walmsley, James; Jayasurya, Philip; Bracey, Tim; Ariyarathenam, Arun; Berrisford, Richard; Humphreys, Martyn Lee; Sanders, Grant; Wheatley, Tim; Chan, David SY
Abstract: Accurate assessment of lymph node involvement is vital in the staging and prognostication of oesophagogastric cancers. Radiological lymph node size is an established criterion for metastatic involvement. Enlarged lymph nodes are generally interpreted as metastatic. However, there is little data on the correlation between lymph node size and metastatic infiltration confirmed on histopathology. This study aims to correlate lymph node size in oeosphageal cancer resection specimens with frequency of metastatic involvement. Regional lymph nodes from oesophagectomy specimens of 32 consecutive patients who had pathologically confirmed N1 disease were analysed from May 2019 to May 2021. The number of positive and negative lymph nodes for each patient were counted. The largest diameter of each positive and negative lymph node was measured. The frequency of metastatic involvement was then calculated and correlated to lymph node size. A total of 956 lymph nodes from 32 patients were analysed. Median age was 73.5 (48-80) years, there were 28 male and 4 female patients and 30 of them had adenocarcinoma with the remaining 2 reported as squamous cell carcinoma. Of 956 nodes, 94 (9.8%) were found to have metastatic involvement. The median size for the positive lymph nodes was 4.16 mm compared to 3.15 mm for the negative nodes (p=0.20). Ninety two percent of involved nodes were less than 10 mm diameter. Ninety four percent of the reactive nodes also measured less than 10mm (p=0.347). There was no significant difference in size between metastatic and reactive lymph nodes with the majority of nodes with metastatic infiltration in oesophageal cancer resection specimens measuring less than 10 mm in diameter. Lymph node size is not a reliable indicator of metastatic involvement in patients with oesophageal cancer.